Metallic nanoparticles for electrocatalytic reduction of halogenated organic compounds: A review. (1st May 2021) - Lou, Yao-Yin; Fontmorin, Jean-Marie; Amrane, A.; Fourcade, F.; Geneste, F.
Highlights: A review on nanoparticles-modified electrodes for reductive dehalogenation. The 3D supports for nanoparticles are compared. Methods to prepare and characterize nanoparticles on porous electrode support. The influence of the electrode material on electro-dehalogenation process is discussed. Recent applications of nanoparticles-modified electrodes to treat halogenated compounds. Abstract: Increasing attention is paid to the degradation of refractory halogenated organic compounds in wastewaters. For this purpose, electrocatalytic reduction process constitutes a promising technology due to its high selectivity. Owing to their well-controlled structure and high specific surface area, nanoparticles have been the subject of many investigations in electrocatalysis. This study presents a general review on nanoparticles-modified electrodes to achieve reductive dehalogenation. The role of the electrode support, especially 3-D Carbon and metallic porous electrodes are first discussed. Then, the methods to prepare metallic nanoparticles on the electrode supports included spontaneous deposition and/or electrodeposition are summarized and the commonly used characterization methods of nanoparticles modified electrodes are also presented. The influence of the electrode material, Ag, Pd, and Cu, as representatives, on electro-dehalogenation process is discussed and compared. Finally, this review also highlights the recent applications of these nanoparticles-modified electrodes for the treatment of halogenated organic compounds in aqueous solutions.